Public Service Quality dan Customer Satisfaction: Mengekplorasi Atribut Kualitas Pelayanan Pada Sektor Publik - Tri Nugraha, Joko; Orbawati, Eny Boedi; Fadlurrahman, Fadlurrahman; Mukti, Ari; Ikhtiara, Seiren (Jurnal Pemerintahan dan Politik, 2024)
The quality of public services is the most important thing to know whether they are successful in fulfilling services. The quality of service reflects the quality of the bureaucracy. The objectives of the study include identifying weaknesses or shortcomings of public service delivery and measuring the tendency of public satisfaction level with public services. Using a survey method with 100 respondents. The analysis technique uses a descriptive statistic. The results showed that there are 3 dimensions of service that need to be improved, including: (1) The dimension of fairness of costs / tariffs in services; (2) The dimension of conformity of service products between those listed in the service standard and the results provided and (3) Dimensions of quality of facilities and infrastructure.